The general theory of crime revisited: comparing the relative effects of parental responsiveness and parental behavioral control on aggressive and nonaggressive antisocial behavior in adolescence - Wang, Hongyu (Deviant behavior, 2023)
Using data collected from middle schools in China in 2018, we extend the general theory of crime beyond its focus on low self-control as the leading cause of all crimes and compare the relative impact of parental behavioral control and parental responsiveness on adolescent antisocial behavior. We highlight the etiological distinctions between aggressive and nonaggressive antisocial behavior and find that maternal responsiveness reduces adolescents’ aggressive antisocial behavior through fostering students’ self-control and reduces nonaggressive antisocial behavior through boosting students’ self-esteem.